The influence of swimming performance on objective and subjective health of men. - Kurko Ya.V. (Pedagogìka, Psihologìâ ta Mediko-bìologìčnì Problemi Fìzičnogo Vihovannâ ì Sportu, 2011)
The dynamics of the objective level (in terms of heart rate) and subjective (using questionnaires) the health of men aged 20-30 years engaged in improving swimming for one year. Shown that improving swimming lessons have a positive impact on objective and subjective health in men. In men, rates of cardiovascular normalized, self-esteem and their health is being adequately аnd the number of complaints about health decreases.